Unveiling the modulation of Pseudomonas aeruginosa virulence and biofilm formation by selective histone deacetylase 6 inhibitors - Barone, Simona; Mateu, Baptiste; Turco, Luigia; Pelliccia, Sveva; Lembo, Francesca; Summa, Vincenzo; Buommino, Elisabetta; Brindisi, Margherita (Frontiers in Microbiology, 2024)
Bacterial infections represent a key public health issue due to the occurrence of multi-drug-resistant bacteria. Recently, the amount of data supporting the dynamic control of epigenetic pathways by environmental cues has triggered research efforts toward the clarification of their role in microbial infections. Among protein post-translational modifications, reversible acetylation is the most implicated in the feedback to environmental stimuli and in cellular homeostasis. Accordingly, the latest studies identified the histone deacetylase 6 (HDAC6) enzyme as a crucial player in the complex molecular machinery underlying bacterial clearance or killing. A very important milestone for the elucidation of the consequence of HDAC6 activity in bacterial infections is herein described, unveiling for the first time the role of a potent HDAC6 inhibitor in interfering with biofilm formation and modulating virulence factors of P. aeruginosa. We demonstrated that compound F2F-2020202 affected the production of some important virulence factors in P. aeruginosa, namely pyocyanin and rhamnolipids, clearly impairing its ability to form biofilm. Furthermore, evidence of possible QS involvement is supported by differential regulation of specific genes namely RhlI, phAz1 and qsrO. The data herein obtained also complement and in part explain our previous results with selective HDAC6 inhibitors able to reduce inflammation and bacterial load in chronic infection models recapitulating cystic fibrosis (CF) phenotype. This study fosters future in-depth investigation to allow the complete elucidation of the molecular mechanisms underlying HDAC6 role in bacterial infections.